HIV/AIDS Stigma and Religiosity among African American Women - Muturi, Nancy W.; An, Soontae (My University, 2010)
African American women are disproportionately affected by HIV/AIDS compared to other ethnicities, accounting for two-thirds (67%) of all women diagnosed with HIV. Despite their increased risk of HIV infection, few studies have been conducted to understand culture-specific factors leading to their vulnerability. Given the central role of religious organizations in African American communities, this study explored whether and to what extent religiosity plays a role in stigma toward HIV/AIDS. A survey of 205 African American women in two Midwestern cities measured the following key variables: 1) religious stigma of HIV/AIDS, 2) religiosity, 3) personal relevance of HIV/AIDS, 4) knowledge of HIV/AIDS, 5) perceived influence of religion on views of people with HIV/AIDS, and 6) demographics. Results of hierarchical regression showed that after controlling for key factors, religiosity was a significant factor predicting the level of religious stigma (β=-.18, p <.05). Those with high religiosity displayed significantly higher stigma, associating HIV/AIDS with a curse or punishment from God. Verbatim responses to an open-ended question also revealed seemingly ingrained prejudice against HIV/AIDS from a religious perspective. The findings point to the important role of faith-based organizations (FBOs) in addressing HIV/AIDS issues within African American communities.
Keywords: HIV/AIDS; Stigma; Religiosity; Faith-based organizations; African American; Women; Spirituality; Culture-Specific approach